A Cytokine Circus with a Viral Ringleader: SARS-CoV-2-Associated Cytokine Storm Syndromes. Issue 12 (December 2020) - Cabler, Stephanie S.; French, Anthony R.; Orvedahl, Anthony
Abstract : An unbridled host immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is likely to underlie severe cases of the disease and has been labeled a 'cytokine storm syndrome' (CSS). Here, we emphasize that categorization of syndromes triggered by a completely novel pathogen based on other seemingly similar, but potentially distinct, known entities is an inherently risky endeavor. Highlights: An uncontrolled host immune response following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and a cytokine storm contribute to severe coronavirus disease 2019 (COVID-19). Among the myriad clinical syndromes identified in patients with COVID-19, multisystem inflammatory syndrome in children (MIS-C) is emerging as a severe complication in pediatric patients. Cohorts of pediatric patients with MIS-C reveal overlapping but distinct pictures from SARS-CoV-2-associated cytokine storm syndrome (CSS) with respect to their clinical and laboratory profile. While candidates for targeted therapies based on understanding of the pathogenesis of SARS-CoV-2-associated CSSs are emerging, and there may be overlap in the pathogenesis and therapy, it is clear that syndrome-specific approaches will be necessary.